Student engagement in foreign language learning: relations with classroom goal structure, self-efficacy, and gender - Wang, Hui; Patterson, Meagan M.; Long, Haiying (Frontiers in Education, 2024)
The present study examined the effects of classroom goal structure, self-efficacy, and gender on student engagement among college students (N = 606) learning English as a foreign language in China. Data analysis using multi-group structural equation modeling found that mastery classroom goal structure impacted male students' engagement both directly and indirectly through self-efficacy, whereas only the indirect path via self-efficacy was significant for female students. Performance classroom goal structure had a significant effect on student engagement for male students but not female students. In addition, self-efficacy can not only impact student engagement but also mediated the relations between mastery classroom goal structure and student engagement regardless of student gender. These findings suggest that creating a classroom environment that highlights the importance of working diligently and holding optimistic beliefs in one's language capacities can promote English learners' engagement across genders. However, a classroom climate that emphasizes demonstrating competence and high performance relative to others might promote engagement for men, but not for women.